Changes in Nigeria’s enabling environment for nutrition from 2008 to 2019 and challenges for reducing malnutrition - Adeyemi, O.; Bold, M. van den; Nisbett, N.; Covic, Namukolo M. (Springer, 2023)
Key 2025 global nutrition targets are unlikely to be met at current rates of progress. Although actions necessary to reduce undernutrition are already mostly known, knowledge gaps remain about how to implement these actions in contextually appropriate ways, and at scales commensurate with the magnitude of the problem. This study describes the nutrition enabling environment in Nigeria, a country that contributes significantly to the global undernutrition burden, and identifies potential entry points for improving the enabling environment that could facilitate implementation and scale-up of essential intervention coverage. Study data were obtained from two sources: content analysis of 48 policies/strategies from agriculture, economic, education, environment, health, nutrition, and water/sanitation/hygiene sectors; and interviews at federal level (16) and in two states (Jigawa (10) and Kaduna (9) States). The study finds that aspects of the enabling environment improved between 2008 and 2019 and facilitated improvements in implementation of nutrition-specific and nutrition-sensitive interventions. Enabling environment components that improved included the framing of nutrition as a multisectoral issue, nutrition advocacy, political attention, evidence around intervention coverage, civil society involvement, and activity of nutrition champions. These factors have been especially important in creating and sustaining momentum for addressing malnutrition. While challenges remain in these aspects, greater challenges persist for factors needed to convert momentum into improvements in nutrition outcomes. Research and data that facilitate shared understanding of nutrition; improved multisectoral and vertical coordination; increased and improved delivery and operational capacity; and increased resource mobilization will be especially important for achieving future progress in nutrition in Nigeria.